PENINGKATAN PEMASARAN PRODUK UMKM MELALUI PEMANFAATAN MARKETPLACE TOKOPEDIA DAN FACEBOOK DESA KROPOH KECAMATAN RAAS KABUPATEN SUMENEP - Misbahul Ulum; Afan Ajemali; Roni Yanto (CV. Denasya Smart Publisher, 2025)
The development of digital technology has opened up new opportunities for Micro, Small, and Medium Enterprises (MSMEs) to expand their marketing strategies through internet-based platforms. This study aims to enhance the digital marketing capacity of MSMEs by providing training on creating online stores via Tokopedia and Facebook in Kropoh Village, Raas Subdistrict. This research uses a descriptive qualitative method with a case study approach. Data was collected through observation, interviews, and questionnaires. The results show that digital marketing training improves the understanding and skills of MSME actors in utilizing marketplaces, and contributes to an average sales increase of 25%. This study emphasizes the importance of digital literacy and technology-based marketing strategies in improving the competitiveness of MSMEs in the Industrial Revolution 4.0 era.